Cele polityki leśnej w Polsce w świetle aktualnych priorytetów leśnictwa w Europie Część 5. Ku nowej strategii rozwoju leśnictwa w Polsce - Kaliszewski, Adam (Leśne Prace Badawcze, 2018)
The aim of this paper was to review and evaluate drafts of forest policy documents that have been developed for the purpose of updating the Polish „National Forest Policy” of 1997, but never entered into force. A total of 14 documents were covered in this analysis including 13 Regional Operational Programmes of the National Forest Policy and the draft of the National Forest Programme (NFP) developed in 2000–2005, as well as nearly 300 recommendations for the „second” NFP, elaborated in 2012–2016. Very soon after the „National Forest Policy” came into force, it turned out that it needed to be adjusted to changing legal, social and economic conditions. The first attempts to revise and amend the document were made already in 2000. As a result, until 2004, 17 Regional Operational Programmes of the National Forestry Policy were developed and, on that basis, until mid-2005 a draft for a new NFP was worked out. However, the draft was neither adopted nor did it ever enter into force. The second attempt to work out the NFP was made in 2012 and resulted in the development of nearly 300 recommendations to the programme. However, to date, the NFP itself has not been finished. Most of the documents examined here refer to the current priorities of the European forest policy, and thus they would close gaps in the Polish „National Forest Policy”. In this context, the recommendations to the „second” NFP are of great importance, because they were prepared through a wide participation of various stakeholders and they refer to a wide range of problems, propose specific legal regulations, as well as indicate directions for further development of the Polish forest sector. However, the completion of the NFP is a matter of political decision that rests with the Council of Ministers.